Determinants of Financial Statement Publication on Regional Government Website (A Study on Government Regency/City in Central Java ) - Sherina Asri Rosita; Hendri Setyawan (International Journal of Economics Accounting and Management, 2024)
This study aims to obtain empirical evidence to explain and describe the influence of political competition, regional spending, and regional government size on the publication of financial reports on regional government websites. This research will involve all district/city governments in Central Java Province in 2022. The sample selection in this research was carried out using a purposive sampling technique , and the sample consisted of 33 districts/cities in Central Java Province. Secondary data used in this research are district and city regional government financial reports (LKPD) in Central Java Province in 2022, which have been audited by the BPK. This data is published through the respective regional government websites . The data analysis used is descriptive analysis and multiple linear regression analysis. This research shows that regional spending, political competition, and government size do not influence the publication of financial reports on regional government websites.